2009
DOI: 10.1016/j.jvs.2008.12.054
|View full text |Cite
|
Sign up to set email alerts
|

Reporting mid- and long-term results of endovascular grafting for abdominal aortic aneurysms using the aortomonoiliac configuration

Abstract: In this retrospective analysis, the aortomonoiliac configuration for elective AAA repair was proven to be safe and efficacious. Midterm and long-term follow-up results in this series compare well with previously reported results for AAA endografting using both bifurcated and aortomonoiliac endoprostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 53 publications
(75 reference statements)
0
16
1
1
Order By: Relevance
“…Indications and specifications for the implantation of each device in this center have been described in detail elsewhere. 3,8,23,24 Whenever a bifurcated endograft could be implanted, the aortouniiliac configuration was avoided because it involves an extra-anatomic bypass. The team of vascular surgeons that performed the operations selected the devices for implant according to the anatomy of the proximal and distal neck, the iliac configuration, and the amount of calcification or thrombus at each landing zone.…”
Section: Methodsmentioning
confidence: 99%
“…Indications and specifications for the implantation of each device in this center have been described in detail elsewhere. 3,8,23,24 Whenever a bifurcated endograft could be implanted, the aortouniiliac configuration was avoided because it involves an extra-anatomic bypass. The team of vascular surgeons that performed the operations selected the devices for implant according to the anatomy of the proximal and distal neck, the iliac configuration, and the amount of calcification or thrombus at each landing zone.…”
Section: Methodsmentioning
confidence: 99%
“…Although a multicentre randomised study showed that late patency was higher after direct bypass than crossover bypass in good-risk patients with unilateral iliac occlusive disease not amenable to angioplasty, 23 the use of AMI endografting combined with crossover bypass grafting compared to bifurcated endografting did not independently increase the risk of major complication during follow-up. 24 Similarly, Lazaridis and co-workers 25 concluded that AMI configuration for elective aneurysm repair has proven to be safe and efficacious. In addition, they reported that long-term follow-up results compare well with primarily reported results for endografting using bifurcated endoprostheses.…”
Section: Discussionmentioning
confidence: 98%
“…Indications and specifications are described elsewhere (15,(17)(18)(19)(20). Procedures were performed in a surgical operating theater under general anesthesia via femoral-artery exposure with low-osmolality nonionic contrast.…”
Section: Methodsmentioning
confidence: 99%